Influence of etiologic factors on speech perception of cochlear-implanted children. (September 2013) - Janeschik, Sandra; Teschendorf, Melanie; Bagus, Heike; Arweiler-Harbeck, Diana
Abstract : Objective: Rehabilitation success in cochlear implant patients is influenced by many factors. Influence of different etiologies of deafness on rehabilitation outcome is assessed. Methods: Study design: Retrospective survey of patients. Setting: University hospital. Secondary referral center. Patients: One hundred and sixty-three between 1996 and 2008 implanted children (0–18 years, mean 5.17 years). Interventions: Evaluation of patients' data: origin of deafness, hearing and speech test results. Access Data Base; Wilcoxon and t- test. Results: Mean follow-up: 65.4 months. Etiology of deafness in children found in 104 cases: 69 (51.9%) suffered from hereditary hearing loss. All children showed improvement in their auditory performance, children with connexin-26 mutation performed significantly best, Usher and CHARGE-syndrome children significantly worst. Post-meningitic and post-septic children developed slower but reached same levels later. Discussion: Primary cause of deafness, among other factors, has a considerable impact on outcome of rehabilitation. This offers possibilities to influence the outcome by etiology-adjusted therapy modules.